A231: effects of a six-week pre-competition program on blood biomarkers in female adolescent rowers - Zhang, W.; Li, F. (International Journal of Physical Activity and Health, 2026)
Rowing is a high-intensity cyclic endurance sport that demands precise regulation of training loads to optimize performance. Adolescent athletes undergoing rapid growth and endocrine changes may respond differently to training than adults. However, most current research focuses on adult rowers, with limited evidence available for adolescent females. This study aimed to evaluate the effects of a six-week pre-competition training program on the blood biochemical markers of adolescent female rowers in order to inform age-appropriate training strategies. Twenty adolescent female rowers (age: 13.9 ± 0.7 years; height: 169.0 ± 4.85 cm; weight: 51.2 ± 11.6 kg) were recruited. The study adopted a pre-post-experimental design over six weeks. All participants followed a standardized pre-competition training regimen. Blood samples were collected in a fasted state before and after the intervention. The following markers were analyzed: Hematological: red blood cell count (RBC), hemoglobin (HGB), hematocrit (HCT), and mean corpuscular volume (MCV). Endocrine: testosterone (T), cortisol (C), and testosterone-to-cortisol ratio (T/C). Metabolic: blood urea nitrogen (BUN) and creatine kinase (CK). Immune: white blood cell count (WBC), immunoglobulin G (IgG), immunoglobulin M (IgM), and immunoglobulin A (IgA). Biochemical parameters were assessed using standard laboratory assays. Paired-sample t-tests were performed using SPSS 27.0 to evaluate pre-post changes, with significance set at P < 0.05. Post-training, all indicators remained within clinical norms. RBC and MCV significantly increased (P < 0.05), while HGB and HCT showed non-significant upward trends. Testosterone and the T/C ratio increased significantly (P < 0.05), whereas cortisol showed a slight, non-significant increase. BUN decreased, and CK increased without reaching significance. WBC slightly decreased, and immunoglobulin levels remained stable. The six-week pre-competition training led to beneficial adaptations in oxygen transport capacity and endocrine response, as evidenced by increased RBC, MCV, and testosterone. Metabolic and immune markers remained unchanged, suggesting that the training load was appropriate and did not induce excessive physiological stress. These results align with prior findings in adolescent athletes but provide new evidence specific to female rowers. Limitations include a small sample size and a short observation period. Future studies should explore long-term effects and larger cohorts. This research offers valuable guidance for designing scientifically grounded training and monitoring protocols in youth rowing.